17 Preclinical Study of Anti-CAIX/CD70 DFIR CAR-T Cell Therapy Secreting Anti-PD-1/CTLA-4 Bispecific Payload for Advanced Clear Cell Renal Cell Carcinoma Treatment - Yufei Wang (The Oncologist, 2026)
Abstract Background Clear cell renal cell carcinoma (ccRCC) remains difficult to cure due to tumor antigen heterogeneity, on-target off-tumor (OTOT) toxicity risks, and a profoundly immunosuppressive tumor microenvironment (TME). While the combination of anti-PD-1 (nivolumab) and anti-CTLA-4 (ipilimumab) demonstrated clinical benefit in intermediate- and poor-risk RCC, durable responses remain limited. CAR-T cell therapy offers a promising approach but is constrained by single-antigen targeting and T cell exhaustion within the TME. We developed the Dual-targeted Fine-tuned Immune-Restoring (DFIR) CAR-T cell therapy to simultaneously address tumor heterogeneity, OTOT toxicity, and TME immunosuppression in advanced ccRCC. Methods Direct stochastic optical reconstruction microscopy (dSTORM) and immunohistochemistry (IHC) were used to quantify expression densities of carbonic anhydrase IX (CAIX) and CD70 across ccRCC tumor stages. An affinity/avidity fine-tuned anti-CAIX CAR moiety (G9) was engineered for preferential elimination of high-CAIX tumor cells while sparing low-CAIX normal tissues. A novel tetravalent bispecific antibody (BsAb) co-targeting PD-1 and CTLA-4 was generated via phage display and antibody engineering. DFIR CAR-T cells were armed with this BsAb as a secreted payload and evaluated in multi-challenge cytotoxicity assays and a humanized ccRCC orthotopic mouse model. Off-target specificity of all four single-chain variable fragments (scFvs) was assessed by Retrogenix screening. GMP-grade manufacturing of DFIR lentiviral vectors (LVVs) was performed to support IND-enabling studies. Results CAIX and CD70 were highly expressed in ccRCC regardless of tumor stage and dual-antigen targeting CAR significantly expanded the target tumor cell population, overcoming antigen heterogeneity. The G9 CAR moiety preferentially eliminated high-CAIX tumor cells while sparing normal tissues, successfully mitigating OTOT toxicity. The novel tetravalent PD-1/CTLA-4 immune checkpoint inhibitor (ICI) BsAb demonstrated superior efficacy compared to the nivolumab and ipilimumab combination. DFIR CAR-T cells demonstrated robust cytotoxic activity and sustained antitumor immunity across multiple challenge rounds, and exhibited enhanced tumor control in a humanized ccRCC orthotopic mouse model. Retrogenix off-target screening confirmed high specificity across all four scFvs. GMP-grade manufacturing of DFIR LVVs yielded high-titer, high-transduction-efficiency vectors, to be validated in GMP-scale DFIR CAR-T cell manufacturing. Conclusions Anti-CAIX/CD70 DFIR CAR-T cell therapy simultaneously addresses three critical barriers to solid tumor immunotherapy — antigen heterogeneity, OTOT toxicity, and TME immunosuppression — and holds promise to achieve durable cures for advanced RCC. Upon completion of the chemistry, manufacturing, and controls (CMC) section, an IND will be submitted to the FDA to initiate a Phase I clinical trial for patients with advanced ccRCC. DOD CDMRP Funding yes